2019
DOI: 10.1080/19359705.2019.1644570
|View full text |Cite
|
Sign up to set email alerts
|

A review of minority stress as a risk factor for cognitive decline in lesbian, gay, bisexual, and transgender (LGBT) elders

Abstract: Lesbian, gay, bisexual, and transgender (LGBT) older adults comprise a unique and growing subset of the aging population. The historical context in which they came of age was imbued with victimization and discrimination. These experiences are subjectively stressful and collectively known as minority stress. Older LGBT adults continue to face stressors related to their gender and sexual identities in their daily lives. Importantly, chronic minority stress (CMS), like other forms of chronic stress, is harmful to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 106 publications
(138 reference statements)
3
59
0
Order By: Relevance
“…Minority stress theory (Meyer, 2003) purports that stressors specific to an LGBT identityfor instance, direct discrimination, fear of stigma, internalized homophobia, and concealment of a minority identityhelps to explain sexual orientation and gender identity differences in health. Indeed, a recent review of the literature showed that exposure to chronic minority stress is related to health declines among LGBT older adults (Correro & Nielson, 2019).…”
Section: Stigma and Housing For Lgbt Older Adultsmentioning
confidence: 99%
“…Minority stress theory (Meyer, 2003) purports that stressors specific to an LGBT identityfor instance, direct discrimination, fear of stigma, internalized homophobia, and concealment of a minority identityhelps to explain sexual orientation and gender identity differences in health. Indeed, a recent review of the literature showed that exposure to chronic minority stress is related to health declines among LGBT older adults (Correro & Nielson, 2019).…”
Section: Stigma and Housing For Lgbt Older Adultsmentioning
confidence: 99%
“…For LGBTIQA+ people with disability, experiences of discrimination and oppression are compounded by intersecting, marginalised experiences and social identities, leading to multiple minority stresses [19]. 'Minority stress' refers to how marginalised groups experience stress that arises from experiences of stigma and discrimination, which leads to increased negative physical and mental health and social wellbeing outcomes [20]. Social support and networks have been shown to be protective factors against poor general health, disability and depression among lesbian, gay and bisexual people [21].…”
Section: Health Outcomes For Lgbtiqa+ People With Disabilitymentioning
confidence: 99%
“…7 Mental health stressors and disorders differ significantly between cisgender and transgender individuals. 8 Mustanski and colleagues have found that among lesbian, gay, bisexual and transgender (LGBT) youth with steadily high or increasing levels of victimization from adolescence to early adulthood were at higher risk for depression and posttraumatic stress disorder. 9 These experiences of victimization and discrimination have been collectively labeled as minority stressors, and have been associated with harm to health and well-being.…”
Section: Commentary: Valuing the Vulnerable -The Important Role Of Trmentioning
confidence: 99%
“…More specifically, these chronic stressors contribute to LGBT health disparities, and increase the risk for cognitive decline. 8 How these stressors interact, if at all, with the neuroanatomy of transgender persons, remains unclear. There are conflicting findings about the neuroanatomy of transgender persons and whether it more closely resembles the neuroanatomy of their natal sex or their gender identity.…”
Section: Commentary: Valuing the Vulnerable -The Important Role Of Trmentioning
confidence: 99%